Progressive dyspnea and signs of right heart dysfunction. Issue 1 (10th January 2017) - Staubach, Stephan; Strohm, Henning; Mudra, Harald
Abstract : A 40‐year‐old woman was admitted due to dyspnea and fever. Transthoracic echocardiography revealed signs of right heart volume overload and vegetations on the tricuspid valve with insufficiency. Transesophageal echocardiography showed a sinus venosus defect (SVD) with significant left‐to‐right shunt. Computed tomography scanning was primarily performed to rule out pulmonary embolism; however, it showed interatrial communication. Due to the concomitant tricuspid insufficiency with additional volume overload, the diagnosis of SVD was more challenging. Usually, transthoracic echocardiography remains the initial diagnostic imaging modality; however, detection rates are very low. Therefore, further imaging is mandatory in unexplained substantial right heart dilatation.